Exotropía y ambliopía en niño de 5 años de edad. - Figueroa Filia, Edson Isacc (2021)
This clinical case is that of a five-year-old male patient with exotropia and amblyopia in the left eye. It is important to evaluate and diagnose as early as possible to avoid serious vision problems, and various methods (either by surgery or vision therapy) should be used to correct them early, because doing so can be very helpful. Optometric and ophthalmologic follow-up of the subjective and objective methods, as well as visual acuity tests (objective refraction tests such as auto refractometers, hirschberg test, simple and unilateral cover test) used in the patient was performed, knowing that there are different types of strabismus and also different causes that can lead to optic nerve injury or even a bad work of the muscles that control the eyeball to avoid visual difficulties that lead to an irreversible loss of vision. The patient presented manifest exotropia with amblyopia in the left eye where the causes of strabismus may be congenital and visual health will depend only on the interest of the child and parents.